Demographics and Disaster Risk Reduction and Management of Government Hospital Nurses in Zambales, Philippines - Kaye Ann A. Bautista; Jestoni D. Maniago (European Scientific Journal, ESJ, 2018)
During times of disaster, hospitals play an integral role within the healthcare system by providing essential medical care to their communities. Any incident that causes loss of infrastructure or patient surge, such as a natural disaster, terrorist act, or chemical, biological, radiological, nuclear, or explosive hazard, often requires a competent response and recovery effort of nurses. This descriptive study aimed to assess the disaster risk reduction and management of government hospital nurses on the components of disaster prevention and mitigation, disaster preparedness, disaster response, and disaster rehabilitation and recovery. The one hundred respondents were randomly selected from the five government hospitals in the province of Zambales, Philippines. The researchers employed various data gathering procedures such as interview and the use of questionnaire. Data were statistically treated using frequency, weighted mean, percentage and ANOVA. The researchers found out that the disaster risk reduction and management by government hospital nurses was frequently practiced. Moreover, it revealed that disaster risk reduction and management has a significant difference on the respondent’s education, training and work experiences. Healthcare systems need to ensure that all healthcare staff including nurses are ready for disaster occurrences. Regardless of the variation of demographic profiles, nurses should know the scope of their responsibility and role in responding to, managing and recovering from disasters impacts.